Culto a la Santa Efigenia: la razón étnica y la utopía social - Arroyo Aguilar, Sabino (2008)
This study is about the ways of the culture identification and the ethnic legitimation through the reinvention of the Santa Efigenia’s Wroship, as the only «Santa Morena» from the Cañete valley, from Lima-Perú and, that these last years is incoming as a cultural force or as a religious icon, associated to the history of the afroperuanos fron colonial origin and of the contemporany Andean inmigrants. Likewise, this study explain now the archetypes works in the act escenary in order to ask for their cultural programs and alternative projects in a changing scenary and an integral develope of the country.